Peningkatan Pemahaman Masyarakat Terhadap Aspek Hukum Credit Union di Kecamatan Ngaliyan Semarang - Endang Setyowati; Dian Prawitasari; Ana Kadarningsih (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
Credit Unions are empowering institutions, which were founded with the aim of controlling the use of money, improving the moral and physical values ​​of each person, and empowering their members to be independent. In line with the government's program to empower Micro, Small and Medium Enterprises (MSMEs), the existence of Credit Unions will really help micro and small economic actors. Credit Unions have the characteristic of being community based. One of the credit unions currently developing in the city of Semarang is Mitra Satuhu Credit Union. Increasing understanding of the legal aspects of Credit Union is carried out with the aim of providing understanding to Credit Union members regarding legal aspects, especially regarding the legal entity status of Credit Union. The methods used in this activity vary, namely: conveying information, interactive, group discussion, and social analysis. Through this activity, it is hoped that it can provide benefits to the community in general and Mitra Satuhu Credit Union in particular.